2015
DOI: 10.1177/1046878115577160
|View full text |Cite
|
Sign up to set email alerts
|

Performance in Tangible and in Cognitive Stock-Flow Tasks

Abstract: Background. Most research in the area of dynamic decision making in general and stock-flow failures in particular is conducted with the help of computerized simulations as task environments or paper-based tasks of simple dynamic systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…This conclusion is in line with a learning difficulty frequently mentioned in systems dynamics literature (Alessi & Kopainsky, 2015; Davidsen & Spector, 2015): that it is difficult to develop an understanding of how the behaviour of a complex system emerges from its underlying causal structure. Particularly, various studies (Alessi & Kopainsky, 2015; Fischer et al, 2015; Strohhecker & Größler, 2015; Sweeney & Sterman, 2000) reported that learners tend to misunderstand stocks and flows. The SCC model used in this experiment involves essentially stock-flow relationships and delays related to the flows and accumulations of product inventories and orders throughout the supply chain system.…”
Section: Resultsmentioning
confidence: 99%
“…This conclusion is in line with a learning difficulty frequently mentioned in systems dynamics literature (Alessi & Kopainsky, 2015; Davidsen & Spector, 2015): that it is difficult to develop an understanding of how the behaviour of a complex system emerges from its underlying causal structure. Particularly, various studies (Alessi & Kopainsky, 2015; Fischer et al, 2015; Strohhecker & Größler, 2015; Sweeney & Sterman, 2000) reported that learners tend to misunderstand stocks and flows. The SCC model used in this experiment involves essentially stock-flow relationships and delays related to the flows and accumulations of product inventories and orders throughout the supply chain system.…”
Section: Resultsmentioning
confidence: 99%
“…The contributions by Bassi, De Rego, Harrisson, and Lombardi, by Strohhecker and Größler (2015), and by Fischer, Degen, and Funke (2015) are more focused on specific aspects of system dynamics as previously discussed. However, it is worth emphasizing that those contributions also have significance for learning and performance.…”
Section: Commentariesmentioning
confidence: 99%
“…Beginning with the experimental articles on important theoretical concerns, three articles (Strohhecker & Größler, 2015; Fischer, Degen, & Funke, 2015; Stave, Beck, & Galvan, 2015) address the comprehension problems people exhibit concerning accumulations (stocks and flows). Not only are these problems at the heart of learning from simulations and games, they affect real-world learning and understanding that have great consequences, such as our failure to develop effective policies for water conservation and mitigation of climate change (subsequently addressed in the articles by Bassi, De Rego, Harrisson, and Lombardi (2015) and Sterman et al, 2015 also in this issue).…”
mentioning
confidence: 99%
“…Strohhecker and Größler (2015) also investigate whether the problems people have understanding stock-flow relationships are due to researchers using abstract tasks (in their case, either graphical or textual presentations). They compared understanding of the relationships in such abstract tasks versus tangible tasks, in which participants worked with and handled actual flasks, funnels, and water to learn about flows, delays, and accumulation.…”
mentioning
confidence: 99%